1971
DOI: 10.1021/jf60175a035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of .alpha.-mercaptol O-(carbamoyl)oximes

Abstract: The selective condensation of a-dicarbonyl comlane-2-carboxaldehyde 0-(methylcarbamoy1)oxime pounds with one equivalent of a dithiol followed by has exhibited especially outstanding greenhouse and oxime formation and subsequent carbamoylation field control of nematodes with no phytotoxicity. has afforded a series of novel a-mercaptol 0-Structure us. activity relationships appear to be (carbamoyl)oximes, some of which possess good consistent with previously studied cholinesteraseto excellent insecticidal, acari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1971
1971
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In addition, dithiolane [384] and isoxazole [385] oximes have been used as acaricides. The O-ethers of thiazole oximes exhibited biocidal activity [386].…”
Section: Oximes Of Five-membered Heterocyclic Compounds With Two Hetementioning
confidence: 99%
“…In addition, dithiolane [384] and isoxazole [385] oximes have been used as acaricides. The O-ethers of thiazole oximes exhibited biocidal activity [386].…”
Section: Oximes Of Five-membered Heterocyclic Compounds With Two Hetementioning
confidence: 99%
“…The replacement of the weakly acidic phenol by another weakly acidic group, such as an aliphatic or alicyclic oxime, in the synthesis broadened the family of the insecticidal carbamates. Further, in order to obtain an optimized acetylcholinesterase inhibition, structure-activity studies showed that conformational similarity to acetylcholine, monomethylation of the carbamate nitrogen, and a-alkylthio substitution were essentials (Fridinger et al, 1971).…”
mentioning
confidence: 99%
“…An interest in the photochemical transformations of oxime carbamates, a class of effective acetylcholinesterase inhibitors (Durden and Weiden, 1974;Fridinger et al, 1971; Friedman and Gemrich, 1971;Fukuto et al, 1969;Magee and Limpel, 1977), provided the impetus for an investigation of 2-methyl-2-(methylthio)propanal 0-[(methylamino)carbonyl]oxime, aldicarb (1) (Payne et al, 1966), which is a contact poison and plant systemic insecticide for a variety of insect species.…”
mentioning
confidence: 99%